Andrey Bely : Spirit of Symbolism. - Malmstad, John E. (Ithaca : Cornell University Press, 2019)
No figure in turn-of-the-century Russia, John Malmstad asserts, better epitomizes the paradoxes of that era than Andrey Bely (1880-1934). Eulogized by Boris Pasternak as "the most remarkable writer of our age" and now widely regarded as the seminal figure in Russian modernism and as one of the major writers of this century, Bely subjected the received standards of truth and value in literature to a penetrating and radical critique. After a long period of suppression under the Stalinist regime, Bely has become the object of growing critical attention in both East and West. Originating in a symposium held in 1984 under the auspices of the Harriman Institute at Columbia University on the fiftieth anniversary of Bely's death, this volume includes ten essays by established scholars of modern Russian literature, including leading Western specialists on Bely. The essays survey Bely's major works in all genres, summarize present research on Bely, reassess critical approaches, and offer fresh interpretations. Analytic summaries of primary works make the essays fully accessible to non-Slavist readers.
Cover; ANDREY BELY; Title; Copyright; Dedication; Contents; Preface; 1. Bely's Symphonies; 2. The Silver Dove; 3. Petersburg; 4. Kotik Letaev, The Baptized Chinaman, and Notes of an Eccentric; 5. Moscow and Masks; 6. Bely's Memoirs; 7. Bely's Poetry and Verse Theory; 8. Bely's Theory of Symbolism as a Formal Iconics of Meaning; 9. Bely the Thinker; 10. Seeing and Hearing Andrey Bely: Sketches from Afar; Bibliography; Contributors; Index
Print version record.
In English.
JSTOR
Keywords: Bely, Andrey, -- 1880-1934 -- Criticism and interpretation -- Congresses; Bely, Andrey, -- 1880-1934; Symbolism (Literary movement) -- Soviet Union -- Congresses; Symbolisme (Mouvement littéraire) -- URSS -- Congrès.; PHILOSOPHY -- Movements -- General; Symbolism (Literary movement); Soviet Union; Conference papers and proceedings; Criticism, interpretation, etc